The Performance of Crowdfunding Model as an Alternative Funding Source for Micro, Small, and Medium-Scale Businesses in Various Countries - Wati, C R; Winarno, A (KnE Social Sciences, 2018)
Crowdfundingis an alternative funding source for micro, small and medium-scale businesses in order to finish the problem of funding for an online campaign. The purpose of this research is to describe the alternative funding source of crowdfunding, by knowing the differences of the success in crowdfunding models and the factors that influence the success level in the achievement of crowdfunding model. The result of this research shows that the highest funding is achieved by the equitybased crowdfunding model. The result also shows that there is a difference in the achievement levels of crowdfunding models. The funding target, the total of backers and the minimum sum of investment affect positively in the success of crowdfunding, while the time range of funding does not affect significantly toward the success of crowdfunding model. Keywords: Micro, small & medium-scale businesses, funding source, crowdfunding